Involvement of Autophagic Pathway in the Progression of Retinal Degeneration in a Mouse Model of Diabetes - Piano, Ilaria; Novelli, Elena; Della Santina, Luca; Strettoi, Enrica; Cervetto, Luigi; Gargini, Claudia (Frontiers in Cellular Neuroscience, 2016)
The notion that diabetic retinopathy (DR) is essentially a micro-vascular disease has been recently challenged by studies reporting that vascular changes are preceded by signs of damage and loss of retinal neurons. As to the mode by which neuronal death occurs, the evidence that apoptosis is the main cause of neuronal loss is far from compelling. The objective of this study was to investigate these controversies in a mouse model of streptozotocin-induced diabetes. Starting from 8 weeks after diabetes induction there was loss of rod but not of cone photoreceptors, together with reduced thickness of the outer and inner synaptic layers. Correspondingly, rhodopsin expression was downregulated and the scotopic electroretinogram (ERG) is suppressed. In contrast, cone opsin expression and photopic ERG response were not affected. Suppression of the scotopic ERG preceded morphological changes as well as any detectable sign of vascular alteration. Only sparse apoptotic figures were detected by TUNEL assay and glia was not activated. The physiological autophagy flow was altered instead, as seen by increased LC3 immunostaining at the level of OPL and upregulation of the autophagic proteins Beclin-1 and Atg5. Collectively, our results show that the streptozotocin induced DR in mouse initiates with a functional loss of the rod visual pathway. The pathogenic pathways leading to cell death develop with the initial dysregulation of autophagy well before the appearance of signs of vascular damage and without strong involvement of apoptosis.